Model Dan Strategi Manajemen Lembaga Pendidikan Islam - Asep Muljawan (STAI Asy-Syukriyyah, 2019)
Islamic education institutions must be able to build a strong Muslim generation, to master science and technology and noble character. To achieve this goal, Islamic education must be managed optimally through Islamic education institutions. This paper attempts to examine the factors that are successful in Islamic education institutions. This study focused on the management of Islamic education institusions to face challenges of globalization. And this research is a quantitative research type of literature study. The results of the literature review show that in managing quality LPI requires a management model, namely the LPI management model with nuance of entrepreneurship, community-based and mosque-based LPI management models. In addition, quality LPI requires management strategies both in general and specifically. Specifically known as strategic management.